1994
DOI: 10.1021/jm00039a014
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of an Unusually Selective and Novel Cocaine Analog: Difluoropine. Synthesis and Inhibition of Binding at Cocaine Recognition Sites

Abstract: Cocaine is a stimulant drug with a high abuse liability. Although it inhibits several monamine transporters in the mammalian brain, its primary mechanism of action has been ascribed to its inhibition of the dopamine transporter. The synthesis, characterization, and receptor binding properties of all eight isomers of a unique tropane analog, 2-carbomethoxy-3-[bis(4-fluorophenyl)-methoxy]tropane is described. In addition, we report that the S-enantiomer, (S)-(+)-2 beta- carbomethoxy-3 alpha-[bis(4-fluorophenyl)m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 17 publications
5
120
0
Order By: Relevance
“…It is noteworthy that previous studies have suggested the existence of different modes of binding for benztropine and cocaine. These compounds are likely to be positioned in a binding site in a different way, based on structure-activity studies showing that the difference between R-and S-enantiomers observed in analogs of cocaine was reversed in fluorinated analogs of 2-carbomethoxybenztropine (35). Vaughan et al (36) observed incorporation of a benztropine-based photoaffinity ligand into a DAT domain encompassing transmembrane regions 1 and 2, as opposed to incorporation of a cocaine-based ligand into a domain containing transmembrane helices 4 -7, again suggesting that the orientation of the compounds in the binding site may differ (35).…”
Section: Table III Potency Of Compounds In Reducing Mtset-induced Inhmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that previous studies have suggested the existence of different modes of binding for benztropine and cocaine. These compounds are likely to be positioned in a binding site in a different way, based on structure-activity studies showing that the difference between R-and S-enantiomers observed in analogs of cocaine was reversed in fluorinated analogs of 2-carbomethoxybenztropine (35). Vaughan et al (36) observed incorporation of a benztropine-based photoaffinity ligand into a DAT domain encompassing transmembrane regions 1 and 2, as opposed to incorporation of a cocaine-based ligand into a domain containing transmembrane helices 4 -7, again suggesting that the orientation of the compounds in the binding site may differ (35).…”
Section: Table III Potency Of Compounds In Reducing Mtset-induced Inhmentioning
confidence: 99%
“…These compounds are likely to be positioned in a binding site in a different way, based on structure-activity studies showing that the difference between R-and S-enantiomers observed in analogs of cocaine was reversed in fluorinated analogs of 2-carbomethoxybenztropine (35). Vaughan et al (36) observed incorporation of a benztropine-based photoaffinity ligand into a DAT domain encompassing transmembrane regions 1 and 2, as opposed to incorporation of a cocaine-based ligand into a domain containing transmembrane helices 4 -7, again suggesting that the orientation of the compounds in the binding site may differ (35). Moreover, there are differences in the psychomotor stimulant-like effects of cocaine and benztropine in rodents (37) and self-administration of these compounds in rhesus monkeys (38).…”
Section: Table III Potency Of Compounds In Reducing Mtset-induced Inhmentioning
confidence: 99%
“…1; Table 2). Of eight possible isomers previously characterized, difluoropine emerged as the most potent within a series of benztropine analogs (Meltzer et al, 1994), and it was 15 times more potent than its progenitor benztropine (Table 2). In further distinction to benztropine, difluoropine displayed low affinity for the muscarinic cholinergic receptor (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…We focused on eight novel, chemically diverse analogs of the phenyltropane CFT, or WIN 35,428, which exhibits high affinity for the DAT ( Table 3; Madras et al, 1989Madras et al, , 1996Madras et al, , 2003Kaufman and Madras, 1991;Meltzer et al, 1994Meltzer et al, , 2001. Selection criteria were initially restricted to high DAT affinity and DAT:SERT selectivity, because SERT inhibitors reportedly attenuate DAT inhibitor-mediated improvements in locomotor activity (Hansard et al, 2002a).…”
mentioning
confidence: 99%
“…Although studies of structure-activity relationships (SAR) did not provide a comprehensive picture of the binding interaction to DAT at molecular level yet, studies on cocaine and its tropane analogues (see Fig. 1) 8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] showed that two…”
Section: Introductionmentioning
confidence: 99%